DISCIPLINAIRIE LIABILITIES OF THE EUROPEAN PUBLIC SERVANTS - Mihaela Tofan; Ana-Maria Bercu (CES Working Papers, 2009)
Work discipline is essential for the proper conduct of business within an organization with implications for productivity and efficiency. Disciplinary liability arises as a direct result of breach of service obligations and rules of behaviour. At EU level, disciplinary responsibility of community public servant is governed by the provisions of the Statute of the European Community published in the Official Journal of the European Community no. L 56 March 4, 1968 and amended on numerous occasions. This paper proposes an analysis of concrete conditions which require disciplinary liability of the European public servant, disciplinary sanctions and procedures for implementing them.